Measurement of the production and elliptic flow of (anti)nuclei in Xe-Xe collisions at √sNN=5.44 TeV - Acharya, S.; Adamova, D.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; et al. (AMER PHYSICAL SOC, 2024)
Measurements of (anti)deuteron and (anti)He-3 production in the rapidity range |y| < 0.5 as a function of the transverse momentum and event multiplicity in Xe-Xe collisions at a center-of-mass energy per nucleon-nucleon pair of root s(NN) = 5.44 TeV are presented. The coalescence parameters B-2 and B-3 are measured as a function of the transverse momentum per nucleon. The ratios between (anti)deuteron and (anti)He-3 yields and those of (anti)protons and pions are reported as a function of the mean charged-particle multiplicity density and compared with two implementations of the statistical hadronization model and with coalescence predictions. The elliptic flow of (anti)deuterons is measured for the first time in Xe-Xe collisions and shows features similar to those already observed in Pb-Pb collisions, i.e., the mass ordering at low transverse momentum and the meson-baryon grouping at intermediate transverse momentum. The production of nuclei is particularly sensitive to the chemical freeze-out temperature of the system created in the collision, which is extracted from a grandcanonical-ensemble-based thermal fit, performed for the first time including light nuclei along with light-flavor hadrons in Xe-Xe collisions. The extracted chemical freeze-out temperature T-chem = (154.2 +/- 1.1) MeV in Xe-Xe collisions is similar to that observed in Pb-Pb collisions and close to the crossover temperature predicted by lattice quantum chromodynamics calculations.
Keywords: LIGHT-NUCLEI PRODUCTION; PB-PB COLLISIONS; CROSS-SECTIONS; PP COLLISIONS; (ANTI-)DEUTERON PRODUCTION; MULTIPLICITY DEPENDENCE; COALESCENCE; ABSORPTION; DEUTERON; QCD; Physics